2021
DOI: 10.4271/09-09-02-0007
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Aided Management of Motorway Facilities Using Single-Vehicle Accident Data

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A more sustainable method to alleviate traffic congestion is to release the reserved capacity (RC) of existing facilities. Numerous studies have demonstrated that the capacity of existing facilities can be significantly improved using methods such as optimal geometric design [8], signal timing [9], traffic management [10,11], and maintenance considering risk profiles [12]. In recent years, the maturity and popularization of autonomous driving technology have provided a new perspective for improving the capacity of existing expressway facilities.…”
Section: Introductionmentioning
confidence: 99%
“…A more sustainable method to alleviate traffic congestion is to release the reserved capacity (RC) of existing facilities. Numerous studies have demonstrated that the capacity of existing facilities can be significantly improved using methods such as optimal geometric design [8], signal timing [9], traffic management [10,11], and maintenance considering risk profiles [12]. In recent years, the maturity and popularization of autonomous driving technology have provided a new perspective for improving the capacity of existing expressway facilities.…”
Section: Introductionmentioning
confidence: 99%